Closing a failed bank resolution practices and procedures - Parker, David C. (David Cameron) 1955- (International Monetary Fund, 2011)
This manual addresses problem bank resolution from the time a bank is identified as being in financial trouble through intervention to liquidation. It comes with an interactive CD-ROM from which users can download and tailor documents to use in their own closing processes. The chapters examine legal frameworks; the function of deposit insurance during bank failures; the importance of public and media relations; measures and procedures used by a supervisory authority to rehabilitate, restructure, or resolve a problem bank; bank intervention procedures; conservatorship operations; bank resolution alternatives and methods for marketing a problem bank using a purchase and assumption agreement; operations and administrative procedures for bank liquidation or receivership; and asset management and disposition.--Publisher's description.